Exploring the Role of Assessment in Shaping Secondary Student-teacher Professionals in Limpopo Province - Thivhavhudzi Muriel Badugela (E-Journal of Humanities, Arts and Social Sciences)
This qualitative research explored the intricate interplay between assessment practices and professional identity formation among student teachers. Professional identity, a multifaceted construct, is examined in the context of teacher education, focusing on unravelling the specific influence of assessment methods. Employing a qualitative approach through in-depth interviews, this study collected comprehensive data from a diverse cohort of student teachers in secondary schools in Limpopo Province. The research sought to identify how formative and summative assessments, feedback mechanisms, and evaluative criteria shape student teachers’ perceptions of themselves as emerging educators. By exploring the impact of assessment on key components of professional identity, including pedagogical beliefs, self-efficacy, and commitment to lifelong learning, the study provides nuanced insights into educational practices that deeply influence the identity formation process. Furthermore, the research explored the potential tension between standardised assessment practices and the individualised nature of teacher identity development. Perspectives from student teachers and mentors were central to elucidating the role of feedback and assessment in fostering a sense of belonging and efficacy within the professional teaching community. The findings will contribute significantly to the qualitative understanding of teacher education and assessment practices, offering valuable recommendations for refining evaluation methods that align with the holistic development of student teachers’ professional identities. The implications of this qualitative study extended beyond academia by providing insights to inform policy and practice and supporting the next generation of educators on their path to becoming proficient and reflective professionals.